Dysregulated miR-222-3p in plasma exosomes of preeclampsia patients and its In vitro effect on HTR8/SVneo extravillous trophoblast cells by targeting STMN1. (2nd November 2022) - Yang, Li-Ping; Zheng, Jia-Hua; Zhang, Jing-Kun; Huang, Xiang-Hua
Objective: To investigate the diagnostic efficiency of miR-222–3p in plasma exosomes (Exos) and plasma for preeclampsia (PE) and the effect of miR-222–3p targeting STMN1 in PE Methods: MiR-222–3p levels in total plasma and plasma Exos were detected in PE patients and healthy controls. A bioinformatics database and dual-luciferase reporter assay were employed to verify the targeting relationship between miR-222–3p and STMN1. Trophoblast HTR-8/Svneo cells were transfected with miR-222–3p inhibitors with/without STMN1 shRNA, followed by MTT, wound healing and Transwell invasion assays. The mRNA and protein expressions were measured by qRT‒PCR and Western blotting, respectively. Results: MiR-222–3p levels in total plasma and plasma Exos were higher in PE patients than in healthy controls, particularly in severe PE patients. In addition, miR-222–3p levels in total plasma and plasma Exos from PE patients were positively correlated with diastolic and systolic blood pressure. The area under the curve (AUC) of miR-222–3p in total plasma for PE diagnostic efficiency was 0.798, with a sensitivity of 76.67% and specificity of 71.93%, while the AUC of miR-222–3p in plasma Exos was 0.708 (sensitivity: 61.67%; specificity: 78.95%). In vitro, miR-222–3p targeted STMN1 in HTR-8/Svneo cells. Low miR-222–3p expression reversed the inhibitory effect of STMN1 shRNA on the proliferation, invasion and migration of HTR/SVneo cells. Conclusion: PE patients had increased miR-222–3p expression in total plasma and plasma Exos, which both have high diagnostic efficiency for PE. MiR-222–3p can target STMN1 to promote the proliferation, invasion and migration of HTR-8/Svneo cells and is a potential therapeutic target of PE.